2015
DOI: 10.5539/elt.v8n11p1
|View full text |Cite
|
Sign up to set email alerts
|

English Digital Dictionaries as Valuable Blended Learning Tools for Palestinian College Students

Abstract: Digital technology has become an indispensible aspect of foreign language learning around the globe especially in the case of college students who are often required to finish extensive reading assignments within a limited time period. Such pressure calls for the use of efficient tools such as digital dictionaries to help them achieve their academic purposes. Efficient use of such tools, however, would not be possible unless students are familiar with their special features so as to use them to their maximum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…On the other hand, no significant differences were found between other types. The result agrees with the other studies reviewed in the literature which found that L2-L1 bilingual dictionaries were used more frequently than other types of dictionaries (Tomaszczyk, 1979;Baxter, 1980;Battenburg, 1989;Schmitt, 1997;Alqahtani, 2005;Ali & Siddiek,2015;Wolter;2015). "L2 learners, even those who have achieved a very high level of L2 proficiency and have been trained in academic skills, including dictionary use, still reach out for a bilingual dictionary" (Laufer and Hadar, 1997:189).It is very obvious that the subjects of the study rely more frequently on L2-L1 bilingual dictionaries.…”
Section: International Journal Of Linguisticssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, no significant differences were found between other types. The result agrees with the other studies reviewed in the literature which found that L2-L1 bilingual dictionaries were used more frequently than other types of dictionaries (Tomaszczyk, 1979;Baxter, 1980;Battenburg, 1989;Schmitt, 1997;Alqahtani, 2005;Ali & Siddiek,2015;Wolter;2015). "L2 learners, even those who have achieved a very high level of L2 proficiency and have been trained in academic skills, including dictionary use, still reach out for a bilingual dictionary" (Laufer and Hadar, 1997:189).It is very obvious that the subjects of the study rely more frequently on L2-L1 bilingual dictionaries.…”
Section: International Journal Of Linguisticssupporting
confidence: 91%
“…In the interview, the students mentioned that they use their mobile to check unknown words either by using dictionaries installed on their mobiles or using Google translator and this shows the high frequent use of mobile and Google translator over other type of dictionaries in terms of the medium. Dwaik (2015) found that the highest reading proficiency is acquired by the students who use online dictionaries. ISSN 1948-5425 2016 It should be noted here that our subjects use print and HHE dictionaries less frequently and the mean frequency is below the middle point.…”
Section: International Journal Of Linguisticsmentioning
confidence: 99%
“…Lastly, Dwaik stated that only 20% of learners use the e-dictionaries in the speaking context (pronunciation as an integral element of the speaking ability). This shows an unusual situation as pronunciation may cause difficulties for subjects participating in the research, and electronic dictionaries would obviously prove to be instrumental in this regard [13].…”
Section: E Dictionaries Help Students Improving Speaking Abilitymentioning
confidence: 99%
“…Mobile devices hold special promise in EFL contexts like Thailand as they can provide students with easy access to up-to-date materials and connect them to the real world and an authenticity of native English that is missing in classrooms led by non-native teachers. Studies have found that in EFL contexts technology can aid the learning of Grammar (Kilickaya, 2013;Saeedi & Biri, 2016) and highest reading proficiency is acquired by students who use online dictionaries (Dwaik, 2015). Moreover, technology and MALL can help teachers transform the language classroom, making English learning more personalized, more interactive, and more accessible (EF EPI, 2016).…”
Section: Mobile Devices and Mall In Efl Contextmentioning
confidence: 99%